EMOTIONAL INTELLIGENCE RELATIONSHIP WITH ACHIEVEMENT LEARNING PHYSICS CLASS X STUDENTS PRIVATE VOCATIONAL SCHOOL OF ST. ALOISIUS RUTENG FOR THE 2019/2020 ACADEMIC YEAR - An Nisaa Al Mu'min Liu; Ana Silfiani Rahmawati; Elenora Yulita Neang (Program Studi Pendidikan IPA FKIP Universitas Jember, 2021)
This study aims for intelligent emotional intelligence with student achievement in learning physics class X SMK Swasta St. Aloisius Ruteng for the 2019/2020 academic year. The type of research used is tracking in a quantitative approach. The population in this study were students of class X Light Vehicle Engineering (TKR) SMK St. Aloisius Ruteng and the sample in this study were class X TKR A assigned to 35 people. With the sampling technique purposive sampling. Retrieval of data, namely questionnaires and documentation. Data analysis used normality test, linearity test and hypothesis test. The result of this study is the absence of emotional intelligence with the learning achievement of students in class X SMK Swasta St. Aloisius Ruteng. This is evidenced by the calculation of the correlation test obtained by 0.010 with a sig α = 0.05, so 0.010 <0.05.